Association between preference for using alcohol beverage-named e-liquids and alcohol use among high school youth. (1st April 2020) - Jackson, Asti; Wu, Ran; Kong, Grace; Camenga, Deepa R.; Morean, Meghan; Simon, Patricia; Bold, Krysten W.; Haeny, Angela M.; Krishnan-Sarin, Suchitra
Highlights: Preference for using alcohol beverage named e-liquids was associated with past-month binge drinking. Preference for using fruit flavored e-liquids was associated with past-month alcohol binge drinking. Candy e-liquid preference was not associated with past-month alcohol binge drinking. Abstract: Background: There are thousands of e-liquid flavors available, and some are named after alcohol beverages (e.g., "pina colada"). It is unclear whether use of e-liquids with alcohol beverage names is associated with adolescent alcohol use. E-cigarettes and alcohol are co-used in adolescents; therefore, it is important to investigate these associations. Methods: Eight Southeastern Connecticut high schools were surveyed in Spring 2015 (N = 7045). We examined the association between preference for using e-liquid flavors and alcohol drinking status (i.e., no past month alcohol use, past month alcohol use but no binge drinking, and past month binge drinking) in ever e-cigarette users (N = 1311). Results: Among ever e-cigarette users who preferred using e-liquids with alcohol beverage names (N = 111), 30.6 % had no past month alcohol use, 19.8 % had past month alcohol use but did not binge drink in the past month, and 49.5 % binge drank in the past month. Multinomial logistic regression (controlling for demographics and including other e-cigarette flavors that were highly endorsed, i.e., fruit and candy) revealed that the preferences of alcohol beverage-named-e-liquid (OR: 2.84, CI: 1.70–4.75) and fruit flavored e-liquids (OR: 1.55, CI: 1.14–2.11), but not candy flavored e-liquids was associated with past-month binge drinking compared to no past-month alcohol use. Conclusion: This evidence suggests that the preference for using alcohol beverage- and fruit-named e-liquid flavors is associated with past-month binge drinking among adolescents. Understanding the associations between alcohol beverage-named e-liquids and alcohol use in adolescents may help inform tobacco regulatory strategies that aim to decrease the use/appeal of e-cigarettes.